Comprehensive outcomes after lung retransplantation: A single‐center review. Issue 6 (3rd June 2018) - Halloran, Kieran; Aversa, Meghan; Tinckam, Kathryn; Martinu, Tereza; Binnie, Matthew; Chaparro, Cecilia; Chow, Chung‐Wai; Waddell, Tom; McRae, Karen; Pierre, Andrew; de Perrot, Marc; Yasufuku, Kazuhiro; et al.
Abstract: Introduction: Lung retransplantation is an important therapy for a growing population of lung transplant recipients with graft failure, but detailed outcome data are lacking. Methods: We conducted a retrospective cohort study of adult lung retransplant in the Toronto Lung Transplant Program from 2001 to 2013 (n = 38). We analyzed the postoperative course, graft function, renal function, microbiology, donor‐specific antibodies (DSA), quality of life, and survival compared to a control cohort of primary transplant recipients matched for age and era. Results: Indication for retransplant was chronic lung allograft dysfunction in most retransplant recipients (35/38, 92%). The postoperative course was more complex after retransplant than primary (ventilation time, 8 vs 2 days, P < .01; ICU stay 14 vs 4 days, P < 0.01), and peak lung function was lower (FEV1 2.2L vs 3L, P < .01). Quality of life scores were comparable, as were renal function, microbiology, and donor‐specific antibody formation. Median survival was 1988 days after primary and 1475 days after retransplant ( P = .39). Conclusions: Lung retransplantation is associated with a more complex postoperative course and lower peak lung function, but the long‐term medical profile is similar to primary transplant. Lung retransplantation can be beneficial for carefully selected candidates with allograft failure.